Properties of Daily Helium Fluxes - Aguilar M; Cavasonza LA; Ambrosi G; Arruda L; Attig N; Barao F; Barrin L; Bartoloni A; Basegmez-du Pree S; Battiston R; Behlmann M; Berdugo J; et al. (AMER PHYSICAL SOC, 2022)
We present the precision measurement of 2824 daily helium fluxes in cosmic rays from May 20, 2011 to October 29, 2019 in the rigidity interval from 1.71 to 100 GV based on 7.6 x 10(8) helium nuclei collected with the Alpha Magnetic Spectrometer (AMS) aboard the International Space Station. The helium flux and the helium to proton flux ratio exhibit variations on multiple timescales. In nearly all the time intervals from 2014 to 2018, we observed recurrent helium flux variations with a period of 27 days. Shorter periods of 9 days and 13.5 days are observed in 2016. The strength of all three periodicities changes with time and rigidity. In the entire time period, we found that below similar to 7 GV the helium flux exhibits larger time variations than the proton flux, and above similar to 7 GV the helium to proton flux ratio is time independent. Remarkably, below 2.4 GV a hysteresis between the helium to proton flux ratio and the helium flux was observed at greater than the 7 sigma level. This shows that at low rigidity the modulation of the helium to proton flux ratio is different before and after the solar maximum in 2014.